Pedagogical Competence and Work Environment as Determinants of Public Elementary School Teachers' Performance in Yogyakarta City - Dakhliatunnaviah Dakhliatunnaviah; Banu Setyo Adi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the effects of pedagogical competence and work environment on teacher performance, both individually and simultaneously, among public elementary school teachers in Yogyakarta City. A quantitative approach with a descriptive design was employed. Data were collected via questionnaires rated on a 4-point scale, and distributed to 200 high-grade teachers selected through quota sampling. Multiple linear regression analysis was conducted using SPSS Statistics 21. The findings reveal that pedagogical competence positively influences teacher performance, contributing 13.5% to improved performance quality. The work environment also has a positive impact, contributing 17.6% to performance effectiveness. When combined, pedagogical competence and work environment explain 31.1% of the variance in teacher performance. These results underscore the importance of both pedagogical competence and a conducive work environment in enhancing teacher performance. Strengthening pedagogical skills enables teachers to implement more effective learning strategies, while a supportive work environment fosters motivation and professional growth. The study highlights the need for policy interventions in Yogyakarta City to enhance teacher competence and improve school environments. Suggested measures include professional development programs, targeted training, and investment in school infrastructure and facilities to create a more supportive educational setting. These initiatives can collectively elevate teacher performance and educational outcomes.